National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages is done by "honorary staff," who receive no monetary payment, but who may thus gain prestige and reputation ; generally it is those who can afford to take this road who find their way to Harley Street and to highly-paid consultant practices. The voluntary hospitals have to wage a perpetual fight for funds. Their income from charitable sources had increased before the present war, but not fast enough to meet their needs ; and nearly a third of them were in debt. During the war, their financial position has been temporarily eased as a result of the State's Emergency Medical Service, which is referred to below. (2) The Public Hospitals were mainly built in the 19th century as Poor Law Hospitals or Institutions, or for infectious diseases. Many are still Poor Law Hospitals, controlled by Public Assistance Authorities. Others have been taken over by the Public Health Committees of County and County Borough Authorities, as Municipal Hospitals. Some of the public hospitals have been developed in recent years to a high standard of efficiency by Municipal Authorities. The public hospitals provide nearly three-quarters of all the available beds in the country, including nearly all the beds for infectious diseases, most of those for tuberculosis, and many for maternity cases. The Ministry of Health exercises only partial control over the policy of these hospitals. (3) During the war the Government has exercised partial control over all hospitals of any size, so as to operate the Emergency Medical Service Scheme which had been roughly planned before the war. Under this Scheme, beds were reserved in each hospital for "E.M.S." cases, such as civilian war casualties and patients from the Forces. The Government has paid for the beds thus reserved. The Scheme has resulted in some grouping of hospitals and in the division of the country into a dozen large areas for administrative purposes. Some such Scheme has been indispensable for war purposes, but the existing Scheme could not meet post-war needs. It is without any adequate democratic control and without plan ; it is largely controlled by representatives of the voluntary hospitals ; and any attempt to make permanent the arrangements which were imposed for war-time purposes would be resented by the authorities in charge of public hospitals. One of the defects of the hospital system as now organised is that the Voluntary Hospitals do not, generally speaking, provide beds for chronic cases, among which the majority are old people ; so that the Local Authorities have to find accommodation for almost all such cases. Reviewing the Hospital Service as a whole, it must be said that it lacks coordination ; it lacks such provision for comprehensive planning as would ensure the location of hospitals where they are most needed and their use for the purposes most required in the national interest; it often lacks adequate provision for prompt and efficient treatment* ; and it also lacks a comprehensive system of financing which would eliminate the present scramble for charity, and would make possible a long-term programme of development. Maternity and Infant Welfare An efficient, co-ordinated service for mothers and for infant welfare is a national necessity, as was shown by the terribly high death-rate of mothers and infants before 1918. The Public Health Act, 1936 (which incorporates the Maternity and Child Welfare Act of 1918), permits Local Authorities to provide Ante-natal Centres for looking after expectant mothers, and Centres for infant welfare. The Midwives Act, 1936, requires Local Authorities to secure the provision of an efficient service of midwives. In practice, some Local Authorities do a lot, others very little. The agencies dealing with maternity in London, for example, are numerous and unco-ordinated. A uniform maternity service, nationally planned and locally administered, is urgently needed. * There is, for instance, a great shortage of beds for the treatment of rheumatic diseases. 36/H24/40